Goobye Eastern Europe by Jacob Mikanowski, Book Review - Phoebe Grace Hardingham (Slovo, 2024)
This is a review of Jacob Mikanowski's 2023 debut monograph Goodbye Eastern Europe. Mikanowksi's central thesis is that Eastern Europe - as an intangible but undeniable geographic and affective location - is disappearing in favour of its aggregate parts. This beautifully written and meticulously researched work acts as both a historical thematic tour through the region and a moving swan song for what Mikanowski sees as a disappearing world.